Potential of rock phosphate use in rubber cultivation - Dissanayake D M A P; Dissanayake T; Maheepala C K; Perera (IRRDB Symposium on Natural Rubber(Hevea brasiliensis) V.1- General, Soils and Fertilization and Breeding and Selection Sessions. Ho Chi Minh City, Vietnam, 14-15 October 1997,p45-53)
The agronomic effectiveness of Sri Lankan Rock Phosphate(ERP) was evaluated for use in both the rubber nursery and in the field with immature and mature rubber plants, in addition to studying the behaviour in rubber soils. Particles of ERP released more P with an increased time for reactions in the soil indicating the suitability of the material for perennial crops. Although the Sri Lankan phosphate rock is heterogeneous in nature, soil acidity governs the dissolution of the minerals present. As the solubility of ERP was naturally low, attempts were made to improve this by beneficiating with different agents, which met with varying degrees of success. When mixed with rubber factory effluent, the increase in the solubility rate was higher in relation to high quality rock phosphate fertilizer than other RP fertilizer grades produced by using the materials from the deposit. Hence, the ability of Sri Lankan rock phosphate to release phosphorus to the soil was more in the presence of rubber factory effluent which further widens the possibility of using the material in the rubber sector. Genotypic variability was evident in the utilization of the Sri Lankan phosphate rock. Plants of high yielding and vigorously growing clones, such as RRIC 110 and 121, utilized the material effectively. The efficiency of ERP in relation to the growth of young plants throughout the immature phase was similar to that of imported Egyptain rock phosphate, TSP and a mixture of the Egyptian and Sri Lankan sources (50:50). Rubber plants fertilized with P from different P sources did not behave differently with respect to their tappability and productivity when they reached maturity. This paper gives an overview of past and current research activities and provides a general assessment of Sri Lankan Rock Phosphate with identification of the stages and conditions that are likely to suit the direct application of the fertilizer material as a source of P in rubber cultivation.
Keywords: Rubber cultivation